(untitled) (Journal of Asian Development Studies, 2025)
Precise writing is an important academic skill that enables learners to summarize information accurately, concisely, and coherently. Teaching of precise writing continues to rely on conventional teacher-centred approaches that often limit student engagement and critical thinking. The present study investigates the effectiveness of innovative teaching methods in improving students’ precis writing skills compared to traditional instructional practices. The study employs a quantitative experimental research design involving forty undergraduate ESL students divided into a control group and an experimental group. Both groups undergo a pre-test to assess their initial precis writing abilities. The control group receives instruction through conventional methods, including lectures, rule-based teaching, and individual practice, while the experimental group is taught through innovative approaches such as collaborative learning, peer feedback, guided summarization, and process-based writing activities. Following a four-to-six-week instructional period, a post-test is conducted to evaluate students’ progress. The findings reveal that students exposed to innovative teaching methods achieve significantly better performance in terms of content accuracy, coherence, organization, grammar, and conciseness than those taught through conventional methods. The study contributes to the field of Applied Linguistics by providing empirical evidence regarding effective pedagogical practices for teaching precis writing and offers practical implications for language teachers, curriculum designers, and educational policymakers.